2010
DOI: 10.14219/jada.archive.2010.0197
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Placement of Restorations on Previously Unrestored Tooth Surfaces by Dentists in The Dental Practice-Based Research Network

Abstract: Objective To identify and quantify the reasons for placing restorations on unrestored permanent tooth surfaces and the dental materials used by Dental Practice-Based Research Network (DPBRN; www.DentalPBRN.org) dentists. Methods A total of 229 DPBRN practitioner-investigators collected data on 9,890 consecutive restorations from 5,810 patients. Information included: (1) reasons for restoring; (2) tooth and surfaces restored; and (3) restorative materials employed. Results Primary caries (85%) and non-cario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 24 publications
4
32
0
1
Order By: Relevance
“…In our study, the use of other filling materials such as GIC and compomer was less than 4%. This is in accordance with a recent study showing that other materials than amalgam and resin composite were preferred by only 5% of 229 US dentists when placing restorations in premolars [Nascimento et al, 2010].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the use of other filling materials such as GIC and compomer was less than 4%. This is in accordance with a recent study showing that other materials than amalgam and resin composite were preferred by only 5% of 229 US dentists when placing restorations in premolars [Nascimento et al, 2010].…”
Section: Discussionsupporting
confidence: 92%
“…In our study the use of other filling materials such as GIC and compomer was less than 4%. This is in accordance with a recent study showing that other materials than amalgam and resin composite were preferred by only 5% of 229 dentists when placing restorations in premolars [Nascimento et al, 2010].…”
Section: Discussionsupporting
confidence: 92%
“…However, within a public system of care (VA), there is no incentive to replace restorations unnecessarily. Further, Nascimento et al (20) found that among private practice providers, 85% of all restorations placed in permanent, previously unrestored teeth were due to caries. Studies evaluating restoration survival rates of direct restorations (amalgam and composite resin) have demonstrated that most restorations are replaced due to recurrent caries (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%